An investigation into the environmental and therapeutic applications of holmium-doped titanium dioxide (Ho-TiO2) nanocatalysts: a kinetic and thermodynamic study of the photocatalytic degradation of Safranin O dye. Issue 1 (1st March 2022) - Jan, F Akbar; Wajidullah,; Ullah, Rahat; Salman,; Ullah, Naimat; Salam, Abdul
Abstract: Titanium dioxide (TiO2 ) and holmium-doped titanium dioxide (Ho-TiO2 ) nanoparticles(NPs) were synthesized through a sol gel route. The synthesized NPs were characterized by ultraviolet-visible (UV–Vis) spectroscopy, x-ray diffraction (XRD), energy dispersive x-ray analysis, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy, and photoluminescence (PL) spectroscopy. DNA binding, antibacterial, hemolysis, and antioxidant assays of the synthesized NPs were also carried out in order to find their therapeutic applications. Successful doping of TiO2 with Ho reduced the bandgap from 3.10 to 2.88 eV. SEM and XRD analysis showed that both TiO2 and Ho-TiO2 NPs exhibit a tetragonal structure and the morphology of the particles improved and agglomeration reduced as a result of doping. The PL emission intensity of TiO2 also reduced with doping. The degradation of Safranin O dye over both the catalysts followed first-order kinetics. The calculated activation energy for the photodegradation of the given dye was found to be 51.7 and 35.2 KJ mol −1 for bare TiO2 and Ho-TiO2 NPs, respectively. After 180 min, 84% and 87% dye degradation was observed using pure TiO2 and Ho-TiO2, respectively. A high percent of degradation of the dye was found at a low concentration (20 ppm) and at optimal dosage (0.035 g) of both the catalysts. The rate of Safranin O dye degradation was found to increase with an increase in temperature and pH of the medium. A DNA binding study revealed that Ho-TiO2 NPs are more capable of binding to human DNA. An antibacterial activity study showed that Ho-TiO2 NPs were more efficient against both gram-negative and gram-positive bacterial strains compared to pure TiO2 . Hemolysis assay showed that TiO2 and Ho-TiO2 NPs are non-biocompatible. Ho-TiO2 NPs showed higher anti-oxidant activity compared to bare TiO2 .